Characterisation of organic inclusions in stalagmites using laser-ablation-micropyrolysis gas chromatography-mass spectrometry - Blyth, Alison; Fuentes, D.; George, S.; Volk, H. (Elsevier, 2014)
Laser-micropyrolysis gas chromatography–mass spectrometry (La-Py-GC–MS) allows the analysis of small targeted areas of organic material. In this proof of concept study a novel application of the technique is demonstrated. Three types of organic matter preserved in speleothems were analysed: dissolved organic matter within the calcite crystal matrix; detrital organic inclusions; and lithified guano derived from birds and bats. The results indicate that there is significant heterogeneity within each sample type, with guano samples having the highest variability. However, there are also distinctive La-Py-GC–MS products that allow separation of the sample types geochemically. These include the chain length distribution within the longer chain n-alkanes (>C20), with the guano sample having a dominance of chain lengths below C27, whilst the other two sample types are dominated by n-alkanes of C27 and above. The detrital inclusion sample has a higher relative abundance of pyrrole and methylpyrroles. A homologous series of longer chain alkylbenzenes is seen only in the guano samples. Our preliminary data indicate that fingerprints of La-Py-GC–MS analyses may be useful to provide information on organic matter preserved in speleothems, but more work is required to extend the technique to lower organic content samples, and to fully test the application in a larger dataset of preserved organic matter types.